Long-Term Mortality Outcomes According to the Frequency of Right Ventricular Pacing in Veterans. (5th May 2010) - Lampert, Brent C.; Moore, Hans J.; Amdur, Richard L.; Karasik, Pamela E.; Lewis, Brian M.; Singh, Steven N.; Fletcher, Ross D.
Abstract : Background . Right ventricular pacing (RVP) has been associated with adverse outcomes, including heart failure and death. Minimizing RVP has been proposed as a therapeutic goal for a variety of pacing devices and indications. Objective . Quantify survival according to frequency of RVP in veterans with pacemakers. Methods . We analyzed electrograms from transtelephonic monitoring of veterans implanted with pacemakers between 1995 and 2005 followed by the Eastern Pacemaker Surveillance Center. We compared all cause mortality and time to death between patients with less than 20% and more than 80% RVP. Results . Analysis was limited to the 7198 patients with at least six trans-telephonic monitoring records (mean = 21). Average follow-up was 5.3 years. Average age at pacemaker implant was significantly lower among veterans with < 20% RVP (67 years versus 72 years; P < .0001 ). An equal proportion of deaths during follow-up were noted for each group: 126/565 patients (22%) with < 20% RVP and 1113/4968 patients (22%) with > 80% RVP. However, average post-implant survival was 4.3 years with < 20% RVP versus 4.7 years with > 80% RVP (P < .0001 ). Conclusions . Greater frequency (> 80%) of RVP was not associated with higher mortality in this population of veterans. Those veterans utilizing < 20% RVP had a shortened adjusted survival rate (P = .0016 ).